Elevated expression of Bmi1 in hepatocellular carcinoma with bile duct tumor thrombi - Zhang, Rui; Xu, Lei-Bo; Zeng, Hong; Yu, Xian-Huan; Wang, Jie; Liu, Chao (Hepato-gastroenterology, 2013)
Hepatocellular carcinoma (HCC) with bile duct tumor thrombi (BDTT) is a rare event. The Bmi1 gene has been reported to play important roles in cancer initiation and progression. In this study, the expression of Bmi1 in HCC with BDTT was investigated. The expression of Bmi1 was examined immunohistochemically in HCC patients with BDTT (B+ group), HCC patients with vascular invasion (V+ group) and combined hepatocellular carcinoma and cholangiocarcinoma (C+ group), respectively. Besides, the Bmi1 mRNA level was investigated by real time PCR in the fresh samples obtained from 13 cases in B+ group, 10 cases in V+ group, and 6 cases in C+ group, respectively. Immunohistochemical staining for Bmi1 showed Bmi1 was highly expressed in the B+ group in comparison with the C+ group and the V+ group, respectively. The Bmi1 mRNA level by real time PCR also showed that it was significantly up-regulated in B+ group compared with those of C+ group and V+ group, respectively. However, there was no statistically significant difference in Bmi1 levels between the subjects with vascular invasion and the subjects without vascular invasion. Bmi1 might play important roles in the development of BDTT in HCC.